Forest Preservation in a Changing Climate REDD+ and Indigenous and Community Rights in Indonesia and Tanzania - Jodoin, Sébastien (Social Sciences, 2017)
This book discusses how a global effort to fight climate change by reducing carbon emissions in the forestry sector in developing countries (known as REDD+) have affected the rights of indigenous peoples and local communities in Indonesia and Tanzania. This title is also available as Open Access.